PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS SISWA SD - Yalvema Miaz (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract: The purpose of this classroom action  research was to describe application of cooperative learning Jigsaw type and to improve learning processes and learning outcomes in the social studies elementary schools' students. Subjects were fifth grade students in the  SDN Baringin Anam Kecamatan Baso Kabupaten Agam. Results found application of the cooperative learning Jigsaw type in teaching social studies included material desription, expert group, home group, and quizz. The application of cooperative learning Jigsaw type improved learning processes and learning outcomes in the social studies elementary schools' students.  Abstrak: penelitian tindakan kelas ini bertujuan untuk mendeskripsikan penerapan pembelajaran kooperatif tipe Jigsaw dan meningkatkan proses dan hasil belajar  IPS siswa SD. Subjek penelitian adalah siswa kelas V SDN Baringin Anam Kecamatan Baso Kabupaten Agam. Hasil penelitian menunjukkan penerapan pembelajaran kooperatif tipe Jigsaw dalam pembelajaran IPS, meliputi penyajian materi, expert group, home group, dan menjawab kuis. Penerapan model kooperatif tipe Jigsaw dapat meningkatkan kualitas proses dan hasil belajar IPS di SD.